2021
DOI: 10.28982/josam.740090
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laboratory parameters between children with and without febrile convulsion

Abstract: Background/Aim: Febrile convulsion is the most common central nervous system disease of childhood. The etiology of febrile convulsion is not fully brightened. In this study, we aimed to evaluate the relationship between hemogram, biochemical and hormonal parameters and febrile convulsion, and the roles of laboratory parameters in its etiopathogenesis. Methods: A total of fifty-four patients diagnosed with febrile convulsion in the pediatric neurology outpatient clinic of a tertiary hospital from October 2017 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In the study of Aydın et al, a significant difference was observed in the MPV value of patients with febrile seizures compared to the healthy control group without fever and seizure. 25 The principal limitations of this study are the low case numbers, its retrospective nature, and the fact that the research employed the hospital database. Further prospective studies with wider population-based case series are now needed to elicit more detailed results.…”
Section: Resultsmentioning
confidence: 97%
“…In the study of Aydın et al, a significant difference was observed in the MPV value of patients with febrile seizures compared to the healthy control group without fever and seizure. 25 The principal limitations of this study are the low case numbers, its retrospective nature, and the fact that the research employed the hospital database. Further prospective studies with wider population-based case series are now needed to elicit more detailed results.…”
Section: Resultsmentioning
confidence: 97%